Motor imagery as a method of maintaining performance in pianists during forced non-practice: a single case study. - Christakou, Anna; Vasileiadis, Georgios; Kapreli, Eleni (Physiotherapy Theory & Practice, 2021)
Background: Musicians suffer from upper limb playing-related musculoskeletal disorders that often oblige them to periodic inactivity. Objectives: To assess the effectiveness of motor imagery as a means of practice when the physical piano practice is restricted. Methods: A 17-year-old healthy pianist participated in a single subject case study with a multiple baseline design (ABC design). Performance ability was assessed during a period of the no practice, then a period of performing motor imagery and again during a period of another no practice. Assessments were performed subjectively by a professional piano teacher and objectively by the Synthesia software. Three visual analog scales were used to record stress, fatigue, and general psychological state. The participant's motor imagery ability was recorded by the use of the Movement Imagery Questionnaire. Results: There was a statistically significant reduction in performance after no practice. There was no change in performance during motor imagery intervention. The pianist's scores moderately correlated with the general psychological state. The Synthesia scoring presented high correlations with professional piano teacher scoring. Conclusions: Motor imagery seemed to have a positive effect in maintaining the musician's performance level. Synthesia shows promise as an outcome measure for assessing music performance, although further research is needed.